Determinants of Employee Performance in Public Training Institutions: Mediating Role of Engagement in the Context of BDK Kemenag RI - Rahmadani, Rahmadani; Rahim, Abdul Rahman; Prasilowati, Sri Lestari; Siradjuddin, Siradjuddin (Universitas Padjadjaran, 2025)
Rhis study examines the influence of Employee Competence (EC) and Organizational Commitment (OC) on Employee Performance (EP), both directly and indirectly through Employee Engagement (EE) as a mediating variable. Civil servants at 14 Religious Training Centers (BDK) under the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI) continue to fall short of the national performance target of 120%, undermining the effectiveness of public service delivery. A quantitative associative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on data collected from 178 civil servants selected through stratified random sampling. The findings reveal that EC and OC significantly affect EP, and both also significantly influence EE. EE itself has a substantial, positive impact on EP. Furthermore, EE significantly mediates the relationships between EC and EP, and between OC and EP. These results highlight EE as the most dominant factor in improving EP and position it as a novel contribution to public sector performance management research. The practical implications suggest that increasing EE can be achieved through training that fosters a sense of ownership, strengthens organizational culture, encourages two-way communication, and recognizes employee loyalty across BDK units within Kemenag RI.